Traditional, complementary, and alternative medicine and the provision of health care to internally displaced persons in South Kivu, Democratic Republic of the Congo - Kazamwali, Muzee; Kisanga, Arsène; Balegamire, Juvenal B.; Kaningini, Euphrasie; Falisse, Jean-Benoît; Furaha, Germaine; Mapendo, Denise M.; Boeyink, Clayton (Frontiers in Human Dynamics, 2024)
Traditional, complementary and alternative medicine (TCAM) providers are central for many when seeking healthcare. Internally Displaced Persons (IDPs) are no exception. This paper seeks to better understand the use of TCAM by IDPs and its connection with the local integration of IDPs into the social fabric of the communities where they have taken refuge. We compare IDPs and non-IDPs access to TCAM providers and their level of confidence in having their healthcare needs met by these sources in Uvira and Kabare territories of South Kivu, Democratic Republic of Congo (DRC).We draw from a mixed method, social connections design comprised of participatory workshops with 111 participants; 847 surveys capturing exploring access and trust of TCAM and other wealth and demographic indicators; 24 interviews with traditional healthcare providers; and 56 in-depth life history interviews with IDPs.We show that IDPs use TCAM more than non IDPs and demonstrate that traditional healers are not monolithic in their characteristics in South Kivu but instead occupy a variety of different roles and occupations, with different prevalences of access and trust from IDPs and non-IDPs. As such, processes of recognition and integration of both IDPs and TCAM providers into formal healthcare systems should be treated cautiously with an understanding of the economic rationales that displaced people and TCAM providers operate under. While many of these TCAM providers are not highly trusted sources in South Kivu, their highly valued treatment of certain conditions such as Buruli ulcer (known locally as "mulonge") suggest there may be potential specific areas where collaboration could be successful between biomedical health workers and TCAM providers.